Mosaic from Aldborough, Boroughbridge, North Yorkshire: the Problem of Its Authenticity - Larionov, Andrei I. (Actual Problems of Theory and History of Art, 2015)
Roman floor mosaic known as the “Capitoline Wolf and the Twins” discovered in 1842 at Lonsdale’s farm of Boroughbridge near Aldborough in North Yorkshire, is discussed in the article. Another piece — known as “The Aldborough Lion mosaic” that depicts a lion under a tree — was discovered at the same farm in 1832. Scholars are positive about its authenticity. Though in size and composition the two mosaics are identical, a detailed study of both comes across certain problems. The owner of the farm — a former mason, sold the “Wolf and the Twins” mosaic to the Literary and Philosophical Society of Leeds 15 years after the find. Caused by such a delay, suspicions around authenticity of Lonsdale’s mosaic grew. H. E. Smith, the author of “Reliquiae Isurianae: the Remains of the Roman Isurium” published it in a Supplement (1867). What makes the case twice suspicious is that the farm owner was a mason who managed the instruments identical to those used by a mosaic-maker. As a professional, not only could he just reassemble the blocks, but was also able to invade the original mosaic-maker’s sphere. In Russian literature the problem of the mosaic’s authenticity has never been discussed before. It is worth mentioning that terms used for mosaic-maker’s instruments are different in Russian and West European languages. Since the appearance and the function of the instruments have been remaining the same during twenty three centuries, one could argue for the usage of the words taglione and tagliolo from antiquity till nowadays. Standardized terminology used in decorative arts has a long history, and gives better understanding to artists and craftsmen from different countries. Twin term «taglione — tagliolo» simply transliterated for Russian-speakers is much more convenient in work at any mosaic workshop.